Progression with clinical features is associated with worse subsequent survival in multiple myeloma. Issue 4 (6th February 2019) - Chakraborty, Rajshekhar; Liu, Hien D.; Rybicki, Lisa; Tomer, Jacqulyn; Khouri, Jack; Dean, Robert M.; Faiman, Beth M.; Kalaycio, Matt; Samaras, Christy J.; Majhail, Navneet S.; Valent, Jason
Abstract : Response rate and survival in multiple myeloma (MM) has improved in the era of proteasome inhibitors and immunomodulatory drugs. However, most patients eventually relapse with biochemical progression (BP) alone or with clinical features of end‐organ damage (CP: clinical progression), with or without extramedullary (EM) disease. We conducted a retrospective cohort study of 252 patients with MM experiencing first relapse (time, T 0 ) to evaluate survival following CP with and without EM as a function of BP. Patients were divided into three groups: BP (n = 134; 53%), CP/EM‐ (n = 87; 35%) and CP/EM+ (n = 31; 12%). The median time from diagnosis to T 0 was significantly shorter in CP/EM+ compared to CP/EM‐ and BP groups (13 vs 25 vs 25 months; P  < 0.001). The incidence of abnormal metaphase cytogenetics at diagnosis was significantly higher in CP/EM+ compared to CP/EM‐ and BP groups (46% vs 18% vs 11% respectively; P  < 0.001). At a median follow‐up of 26 months from T 0, median overall survival was 50, 19 and 10 months for BP, CP/EM‐ and CP/EM+ groups, respectively ( P  < 0.001). On multivariable analysis, pattern of progression was a significant prognostic factor for OS (HR for CP/EM‐ vs BP: 3.6 ; CP/EM+ vs BP : 8.7 and CP/EM+ vs CP/EM‐ : 2.42; P  < 0.001 for all comparisons), along with age at T 0 . In conclusion, progression pattern is an important prognostic factor in the current era, with subsequent survival being dismal in patients with end‐organ damage or EM disease at relapse. Clinical trials in relapsed MM should consider reporting patterns of progression at baseline to ensure balance between study arms.